Effects of high-intensity interval training program on pituartry function in basketball players: a randomized controlled trial - Soslu, Recep; Uysal, Abdullah; Devrilmez, Meltem; Can Çuvalcıoğlu, İsmail; Doğan, Ali Ahmet; Karaburgu, Sülbiye; Taş, Murat (Frontiers in Physiology, 2023)
The aim of the study was to determine how the short high-interval training program affects cortisol levels in basketball players. A total of 27 male basketball players volunteered for the study and were randomly assigned to one of two groups: Control Group (CG) (n = 13, mean age; 20,56 ± 1,45 years, mean height; 184,53 ± 6,65 cm) and Experimental Group (EG) (n = 14, mean age; 20,71 ± 2,12 years, mean height; 86,51 ± 8,21 cm). The experimental group received a 7-week interval training program. Blood samples were taken at the beginning and end of the study. Cortisol, Adrenocorticotropic Hormone, Triiodothyronine, Tetraiodothyronine, Parathyroid Hormone, Thyroid Stimulating Hormone, Insulin, and Glucose levels were measured of the EG and CG. To test the differences between groups and compare the effects of pre and post-intervention, a two-way ANOVA for repeated measures was used. Consequently, the post-test levels of TSH, PTH, and ACTH in the exercise group showed a significant difference when compared to the pre-test values (p = 0.000). Moreover, the post-test levels of Glucose, Cholesterol, Triglyceride, HDL, and Mg in the exercise group showed statistical significance when compared to the pre-test values (p = 0.000). Significant differences were seen in the post-test PTH and ACTH levels of the control group when compared to the pre-test values (p = 0.000). Furthermore, the exercise group showed significant differences in post-test values for HDL and Cholesterol compared to the pre-test (p = 0.000). In addition, when comparing the post-test values and pre-test values of both the exercise group and the control group, it was found that all parameters, with the exception of Ca, exhibited substantial differences in favor of the exercise group. It may be claimed that the implementation of interval training has favorable outcomes on pituitary function parameters. Additionally, the regulation of energy consumption during exercise is favourably influenced, along with the reduction of physiological stress resulting from prolonged exercise.